The Separation of Powers - Kruzslicz, Péter (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
The constitutional principle of the separation of powers and the doctrine behind the principle are as fundamental as they are complex. Three main reasons are behind this complexity. Firstly, a doctrine and a proper theory based on which the doctrine and the principle are developed hide behind the principle. Secondly, by its nature, the concept of the separation of powers is related to the more general constitutional principle of the rule of law. Even though the rule of law appeared mainly after the separation of powers, as a more abstract principle, it also encompasses its constitutional requirement. At the same time, the substance of the separation of powers concerns the institutional organisation of the state despite its above-mentioned relation to the more general principle of rule of law. Thirdly, the functions of the branches of power that are to be separated according to the principle are radically different. Regarding the three main branches, it is obvious that while the judiciary asks for complete independence, a logical gap exists between legislative and executive powers, with the first one being general when the legal norms are adopted and the second one being concrete when it proceeds to the implementation of the norms. Hence, their separation is not so evident, and the principle may require an equilibrium by balancing those powers. Finally, the last reason for the complexity inherent in the concept of separation of powers is due to the different approaches used for the interpretation of the principle. On one hand, it can convey the institutional meaning of separation of bodies, and on the other hand, it can be more functional if an equilibrium is to be maintained while exercising different state functions. As with all constitutional principles, the founding theory of the separation of powers should be analysed in the larger context in which it developed. It is strongly linked to what Montesquieu thought to be the English constitutional regime, even though he was obviously misreading the actual political context. It was implemented – not for the first time but with the most important consequences – in the newly established constitutional regime of the United States of America, and of course, the impact of the American context was greatly influenced the result of its implementation. When it comes to analysing the separation of powers in the context of contemporary states of the Central European region, those contextual facts should also be noticed. In addition, for this region of interest, in a comparative constitutional study, it is also important to notice that a voluntary implementation of an already well-developed principle in a new or different political context can lead to confusing results. Central European states have a particularly rich constitutional heritage, e.g. the Constitution of Poland and Lithuania was among the first to implement the separation of powers as contemporary constitutional regulation, and the principle could be reintroduced in the very foundations of the legal order of Poland when socialist regime disappeared. When doing so, the constituent power of Central Europe could not only use the well-established theory and doctrine of the separation of powers, but it was also aware of and used the already existing constitutional solutions of other constitutional states for the implementation of the principle. However, the exportation of constitutional models to a different context can result in discrepancies in the political praxis. According to the main hypothesis of this chapter, the separation of powers as implemented in the Central European region leads to the rise of strong executive powers. This pheonomenon is independent of the presidential or the parliamentary character of the regimes. On the contrary, a strong executive power is even more common in parliamentary regimes. In addition, if there is a general, international tendency towards the strengthening of executives for many reasons, the emergence of strong executives in the region can also be read as a consequence of Central European traditions and a special need for such strong governments in the particular political context of the region. On one hand, Central European states have struggled with important political, social and economic challenges during their modern history, often demanding a strong and stable executive. They did so to spare themselves of political difficulties which can result from a permanent governmental crisis due to the lack of strong leadership. Some of them also had a negative historical memory of the excessively strong parliamentarism causing such difficulties. On the other hand, a permanent need for reforms – especially after the change of regimes – also required a strong political executive that would be able not only to propose but especially to implement such reforms with success. Thus, even for states such as Hungary or Croatia, which benefitted from an important tradition of parliamentarism under the dualist regime of the Habsburg empire, after the cataclysms of the twentieth century, a stronger executive seemed to be a good solution. However, implementing the separation of powers can be difficult in such a political and constitutional background and may call for special arrangements to guarantee the very fundamental aim of the principle: creating a legal obstacle to the concentration of power. KEYWORDS: separation of powers, checks and balances, concentration of power, institutional equilibrium, constitutionalism and rule of law.